A Technology Acceptance Model (TAM) towards use Intention of E-wallet Among Youth in Malaysia (Revista Galega de Economía)
Consumers are adopting digital payment using financial technology as a result of the development of e-wallet systems. A mobile device's e-wallet application enables users to download payment cards. The use of e-wallet apps as a substitute for traditional payment methods has recently become more popular among users. An E-wallet user doesn't have to carry cash or a credit card with them at all times. A more convenient way of purchasing is possible using this e-wallet. The Technology Acceptance Model (TAM) of E-wallet adoption among Malaysian youth is examined in this research along with the factors that influence them to use an e-wallet. This TAM serves as underpinning for the research framework. The SmartPLS-SEM approach is used to analyze the proposed research framework. The technology acceptance model consists of â€œperceived usefulness, perceived ease of use, and perceived security have positive and significant relationships with behavioral intention to use an e-walletâ€. This outcome contributes to a deeper understanding of the value of utilizing an e-wallet for transactional reasons by the government and service providers in the digital market